Maternal carriers of the ANXA5 M2 haplotype are exposed to a greater risk for placenta-mediated pregnancy complications - Aranda, Federico (2018)
Purpose Annexin A5 (ANXA5) is a protein abundantly expressed in normal placenta where it contributes to the healthy outcome of a pregnancy. Lower ANXA5 levels have been observed in M2/ANXA5 haplotype carrying chorion. Consequently, this study aimed to assess the potential association of M2 maternal carrier status with the risk of recurrent pregnancy loss (RPL), the timing of miscarriages, and other obstetric complications, for the first time in a population from Latin America. Methods This study was designed as a prospective recruitment of RPL patients with post hoc analysis. The distribution of the M2/ANXA5 haplotype was compared between a group of 229 Argentine women with RPL and 100 parous controls, and was further analyzed in subgroups of patients stratified according to the timing of miscarriages and in relation to other obstetric complications. Results No significant differences were found in the distribution of M2 haplotype among either RPL patients or the subgroups with embryonic, early fetal, or late fetal losses compared to parous controls. Notwithstanding, maternal M2/ANXA5 was found to be independently associated with a higher risk of suffering intrauterine growth restriction (IUGR) and/or preeclampsia (PE). Simultaneously, the presence of inherited and/or acquired thrombophilia also proved to be an independent risk factor for these. Conclusions The association found between the maternal carriage of the M2/ANXA5 haplotype and an elevated risk of IUGR and/or PE supports the hypothesis that carrier status of this haplotype and the consequently reduced placental ANXA5 expression might be responsible, at least partially, for the onset of these gestational vascular complications.